(3GdWQjbI GdeMeOjIs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYdfG CeI hSWG NjQ CeehHYO aEf GdYbd hGdfbd eJhGabGf hGdcJGH hGdSfI eJWGHbGfaCQOJ Cf CUfa GdWQjbI GdeMeOjIs
(3BNQgG (B:s
(3hbO HjfG Pdc aj QSGFdfG GdSja GdUGQe hEfbGP GdgGdcjf hEjbGX GdfGFejf hLdGA GdbdhH aYdjc HgG hWGdYgG MJi JYde MbjbI ebGdfG hfbhd GdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3cTa GdXfhf(B: 2 / 1111s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs